2022
DOI: 10.3389/fmicb.2022.914036
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights Into the Phylogeny and Biotechnological Potential of Weissella Species

Abstract: In this study, the genomes of the Weissella (W.) beninensis, W. diestrammenae, W. fabalis, W. fabaria, W. ghanensis, and W. uvarum type strains were sequenced and analyzed. Moreover, the ability of these strains to metabolize 95 carbohydrates was investigated, and the genetic determinants of such capability were searched within the sequenced genomes. 16S rRNA gene and genome-based-phylogeny of all the Weissella species described to date allowed a reassessment of the Weissella genus species groups. As a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 87 publications
3
14
0
Order By: Relevance
“…Considering both the probiotic and safety assessments of the six type strains, it can be concluded that P. beninensis LMG 25373 T is a safe potential probiotic strain. This strain in a previous study ( 2 ) showed the widest consumption of carbon sources. Indeed, among the six type strains tested, P. beninensis LMG 25373 T was the only one capable of using d -galactose (indeed, it was found to harbor the galA gene, encoding α-galactosidase [EC 3.2.1.22] [KAK10_01740], which hydrolyzes α-1,6-galactoside linkages found in sugars such as raffinose, melibiose, and stachyose and branched polysaccharides like galactomannans and galactoglucomannans), α- d -lactose, lactulose, d -melibiose, β-methyl- d -galactoside, d -raffinose, sucrose, pyruvic acid methyl ester, and UMP ( 2 ).…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Considering both the probiotic and safety assessments of the six type strains, it can be concluded that P. beninensis LMG 25373 T is a safe potential probiotic strain. This strain in a previous study ( 2 ) showed the widest consumption of carbon sources. Indeed, among the six type strains tested, P. beninensis LMG 25373 T was the only one capable of using d -galactose (indeed, it was found to harbor the galA gene, encoding α-galactosidase [EC 3.2.1.22] [KAK10_01740], which hydrolyzes α-1,6-galactoside linkages found in sugars such as raffinose, melibiose, and stachyose and branched polysaccharides like galactomannans and galactoglucomannans), α- d -lactose, lactulose, d -melibiose, β-methyl- d -galactoside, d -raffinose, sucrose, pyruvic acid methyl ester, and UMP ( 2 ).…”
Section: Discussionmentioning
confidence: 60%
“…The EPS production influences the biochemical properties of the cell, including hydrophobicity and surface charge; EPS stabilizes microbial biofilm, enhancing bacterial adhesion and aggregation and increasing the tolerance to environmental stress ( 45 ). The consumption of sucrose and raffinose by P. beninensis LMG 25373 T was previously demonstrated ( 2 ), and only this strain was able to produce EPS in MRS agar supplemented with sucrose.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations